Method for preparing sub-millimeter superparamagnetic ferroferric oxide colloidal nanocrystal clusters

CN122658875BActive Publication Date: 2026-10-27NANCHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611150069.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27
Estimated Expiration
2046-07-31

AI Technical Summary

Technical Problem

但在现有技术中,四氧化三铁多以随机分散形式存在于基体内部或表面,缺乏从微观到宏观的结构调控机制,难以在颗粒尺寸增大的同时保持均一的磁响应性能

Benefits of technology

(1)以高球形度纤维素微球作为专属内核基底,通过对纤维素微球内部孔道及表面结构的均一活化,使氨基等活性位点在微球内部及内核区域均匀分布,为Fe3O4纳米晶的优先成核提供反应位点,从而区别于现有技术中磁性颗粒随机包埋或表面附着的复合方式;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122658875B_ABST
    Figure CN122658875B_ABST
Patent Text Reader

Abstract

The application belongs to the field of functional magnetic composite material and nanostructure regulation and control, and provides a preparation method of sub-millimeter superparamagnetic ferroferric oxide colloidal nanocrystal clusters. Through multi-scale assembly and interface regulation, ordered or quasi-ordered aggregation of nanoscale ferroferric oxide grains in the sub-millimeter scale range is realized. The structure still maintains superparamagnetic characteristics while significantly enlarging the particle size, showing low remanence, low coercivity and super-fast magnetic response behavior, thereby breaking through the technical bottleneck that traditional magnetic particles are prone to form magnetic domains during size enlargement, resulting in enhanced magnetic hysteresis. Compared with traditional micron-sized magnetic microspheres, the obtained sub-millimeter colloidal nanocrystal clusters have both the easy controllability of macroscopic particles and the superparamagnetic response characteristics of nanometer units, have higher response efficiency and faster separation speed under the action of a magnetic field, and can quickly recover to a dispersed state after the magnetic field is removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional magnetic composite materials and nanostructure regulation technology, and particularly relates to a method for preparing submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters. Background Technology

[0002] Magnetic functional materials have significant applications in fields such as bioseparation, pharmaceutical delivery, and environmental remediation. Among these, superparamagnetic materials, capable of rapid response under an applied magnetic field and maintaining good dispersion after the magnetic field is removed, are particularly crucial. With evolving application demands, material particle sizes are gradually expanding from nanometer and micrometer scales to larger scales to improve operational convenience and separation efficiency. However, during size scaling, magnetic materials tend to transform from single-domain structures to multi-domain structures, leading to enhanced remanence and intensified hysteresis, making it difficult to maintain superparamagnetic characteristics on a macroscopic scale. Therefore, how to construct magnetic materials with controllable structures while maintaining superparamagnetism over a large size range has become a core problem urgently needing to be solved in this field.

[0003] Cellulose, as a natural polymer material, possesses excellent biocompatibility, biodegradability, and porous structure, and is often used as a supporting matrix for magnetic composite materials. Magnetic composite microspheres formed on this basis combine structural support and magnetic response functions, offering advantages in applications such as magnetic separation. However, existing cellulose-based magnetic microspheres mostly introduce magnetic particles through physical embedding or surface loading, resulting in uneven distribution of magnetic components within the matrix, leading to agglomeration or detachment, and making it difficult to form a structurally continuous and synergistically responsive magnetic system. Iron(III) oxide (Fe3O4) is widely used to construct magnetic composite materials due to its excellent superparamagnetism, low toxicity, and ease of preparation. However, in current technologies, Fe3O4 often exists in a randomly dispersed form within or on the surface of the matrix, lacking a structural control mechanism from microscopic to macroscopic levels, making it difficult to maintain uniform magnetic response performance while increasing particle size.

[0004] The following defects exist in the construction of superparamagnetic magnetic materials in the prior art: (1) The lack of an ordered assembly structure starting from nanounits leads to uneven distribution and local agglomeration of magnetic components at the microscale, making it impossible to form a continuous multi-scale magnetic response network, thus limiting the overall magnetic response efficiency; (2) As the particle size expands from the micrometer scale to a larger scale, traditional magnetic materials are prone to forming multi-domain structures, which manifests as enhanced remanence and intensified hysteresis effect, making it difficult to maintain superparamagnetism at the macroscale, thus limiting the application of materials in the field of rapid reversible magnetic manipulation; (3) In existing magnetic composite particles, the magnetic components and the matrix are mostly unstable or simple composites, lacking an effective interface control mechanism, which leads to difficulties in the use process. (4) Existing preparation methods are difficult to achieve controllable assembly of magnetic nanounits in three-dimensional space, and cannot construct a structural system with continuous transition from the inside to the outside, resulting in uneven internal structure of particles, non-coordinated magnetic response force, and affecting magnetic separation efficiency and response speed; (5) In the process of increasing the content of magnetic components, existing technologies often sacrifice the integrity of material structure or functional stability, and it is difficult to simultaneously take into account high magnetic response performance and structural stability; (6) Existing preparation processes are complex, have narrow process control windows, and are highly dependent on reaction conditions, making it difficult to achieve stable control of structure and performance, resulting in poor consistency between batches of products. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing sub-millimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters, aiming to solve the problems mentioned in the background art.

[0006] In a first aspect, the present invention provides a method for preparing submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters, comprising the following steps: Step S1: Preparation of cellulose microspheres S101. Weigh sodium hydroxide, urea and distilled water, prepare an aqueous solution of sodium hydroxide / urea under ice bath conditions, and then pre-cool at -20℃. S102. Under ice bath conditions, cellulose powder is added to an aqueous solution of sodium hydroxide / urea and stirred to obtain a cellulose solution with a volume fraction of 4%. S103. Weigh out liquid paraffin and Span 80, mix and stir, then inject the cellulose solution into it and continue stirring to obtain cellulose aqueous droplets with controllable particle size. S104, heat the aqueous phase of cellulose with controllable particle size at 50℃, then add epichlorohydrin, continue heating, then add polypropylene glycol glycidyl ether, and continue heating. S105. Stop heating and stirring, add deionized water and let stand to separate the layers. The upper layer is the oil phase and the lower layer is the water phase. The lower layer is milky white, which means that the cellulose microspheres are in the lower layer. After washing, add 1% ethylenediamine solution and activate at 37°C. After washing, transfer to ethanol for storage to obtain amino-activated cellulose microspheres with controllable particle size. Step S2: Preparation of submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters S201. Add FeCl3·6H2O to an ethylene glycol solution and sonicate at 45°C to obtain solution A; add sodium acetate to an ethylene glycol solution and stir magnetically at 55°C to obtain solution B; add sodium citrate to an ethylene glycol solution and stir magnetically at 55°C to obtain solution C. S202. Add solution B to solution A and mix well. Then add solution C and PEG400-2000 at the same time. Sonicate at 25-45℃ to obtain the reaction precursor solution. S203. The cellulose microspheres pre-dispersed in the ethylene glycol phase are added to the reaction precursor solution and reacted at 200°C to form a magnetic composite structure. S204. After the reaction is complete, the supernatant is removed by an external magnetic field separation method, the solid product is collected, and after washing, the precipitate is collected by magnetic separation method to obtain submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters.

[0007] Furthermore, in S101, the mass ratio of sodium hydroxide: urea: distilled water is 7:12:81.

[0008] Further, S103 is specifically as follows: Weigh 80ml of liquid paraffin and 20ml of Span 80, mix them and add them to a three-necked flask, stir at 400rpm for 1h; take 15ml of cellulose solution, use a syringe pump to inject it into the three-necked flask at a speed of 1~15ml / h through a microporous membrane, and continue stirring for 8h to obtain cellulose aqueous droplets with controllable particle size.

[0009] Furthermore, in S105, activation is performed at 37°C for 24 hours.

[0010] Further, S201 specifically involves: taking 27 mL of ethylene glycol solution and placing it in a container, adding 1-8.64 g of FeCl3·6H2O, and sonicating at 45°C for 5-20 min to obtain solution A; taking 27 mL of ethylene glycol solution and adding 1-8.52 g of sodium acetate, and reacting at 55°C with magnetic stirring at 650 rpm for 1 h to obtain solution B; taking 108 mL of ethylene glycol solution and adding 1-2.82 g of sodium citrate, and reacting at 55°C with magnetic stirring at 650 rpm for 1-5 h to obtain solution C.

[0011] Further, S202 specifically involves: adding solution B to solution A and mixing thoroughly, then adding solution C, and simultaneously adding 5-413 mg of PEG400-2000, and sonicating at 25-45℃ for 30-60 min to form a homogeneous and stable reaction precursor solution.

[0012] Furthermore, in S203, the reaction is carried out at 200℃ for 8-24 hours.

[0013] Furthermore, in S204, magnetic separation washing is performed twice each using deionized water and 50% ethanol solution.

[0014] Secondly, the present invention provides submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters, which are prepared by a method for preparing submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters.

[0015] Thirdly, this invention provides the application of submillimeter-scale superparamagnetic iron oxide colloidal nanoclusters in the rapid magnetic separation and enrichment of diagnostic antibodies.

[0016] The present invention has the following effects: (1) Using high sphericity cellulose microspheres as a dedicated core substrate, the uniform activation of the internal channels and surface structure of the cellulose microspheres enables the amino and other active sites to be evenly distributed inside the microspheres and in the core region, providing reaction sites for the preferential nucleation of Fe3O4 nanocrystals, thus distinguishing it from the composite method of random embedding or surface attachment of magnetic particles in the prior art. (2) Based on the growth mechanism of core assembly, Fe3O4 magnetic particles are nucleated from the active sites inside the cellulose microspheres and assembled and grown layer by layer from the inside to the outside in space to form a continuous, dense magnetic coating layer structure without obvious agglomeration, thereby constructing a stable sub-millimeter-scale superparamagnetic iron oxide colloidal nanocrystal cluster. (3) By controlling key parameters such as precursor concentration, reaction temperature and reaction time in the reaction system, the Fe3O4 coating thickness and magnetic load can be controlled, which significantly improves the uniformity of magnetic distribution and makes the force under the action of magnetic field more consistent, thereby significantly improving the magnetic response efficiency and magnetic adsorption performance. (4) An in-situ generation and coating process based on an aqueous system is adopted to achieve controllable growth and structural regulation of Fe3O4 from the core of cellulose microspheres while avoiding complex organic solvent systems, which significantly improves the repeatability and batch consistency of the preparation process. (5) The resulting submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters exhibit high sphericity, narrow particle size distribution, and structural uniformity. Under the action of an external magnetic field, they demonstrate rapid response and efficient separation capabilities, while maintaining good dispersion stability after the magnetic field is removed. They can be widely used in bioengineering (rapid magnetic separation and enrichment of proteins, nucleic acids, and cells; enzyme immobilization carriers), medicine (magnetically controlled targeted delivery systems and magnetic resonance imaging enhanced probes), environmental remediation (efficient magnetic adsorption and removal of heavy metal ions and organic pollutants), and magnetic catalysis. Products based on this structure include high magnetic response bioseparation magnetic beads, magnetically controlled targeted delivery microspheres, and efficient magnetic adsorption functional materials. Attached Figure Description

[0017] Exemplary embodiments of the present invention can be more fully understood by referring to the following figures: Figure 1 An optical microscope image of the submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters prepared in Example 1 of this invention.

[0018] Figure 2 This is a scanning electron microscope (SEM) image of the submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters prepared in Example 1 of the present invention.

[0019] Figure 3 This is a demonstration diagram of the magnetic response speed of the submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal cluster prepared in Example 1 of the present invention.

[0020] Figure 4 This is a particle size distribution diagram of the sub-millimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters prepared in Example 1 of the present invention.

[0021] Figure 5 This is an adsorption state diagram of the submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters prepared in Example 1 of the present invention when an external magnetic field is applied to a large volume of deionized water. Detailed Implementation

[0022] To make the technical problems, solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. The specific embodiments described herein are merely illustrative and are not intended to limit the scope of the invention.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention.

[0024] Example 1: 1. Preparation of cellulose microspheres (1) Weigh 7g sodium hydroxide, 12g urea and 81g distilled water, and dissolve sodium hydroxide and urea in distilled water in sequence under ice bath conditions to obtain an aqueous solution of sodium hydroxide / urea. (2) Pre-cool the sodium hydroxide / urea aqueous solution at -20°C for 12 hours (overnight pre-cooling). (3) Under ice bath conditions, cellulose powder was added to an aqueous solution of sodium hydroxide / urea and stirred at 1000 rpm for 2 hours with a magnetic stirrer to obtain a cellulose solution (4% volume fraction). (4) Weigh 80ml of liquid paraffin and 20ml of Span 80, mix them and add them to a three-necked flask. Set the speed to 400rpm and stir for 1h. (5) Take 15 ml of cellulose solution and inject it into a three-necked flask through a microporous membrane at a speed of 15 ml / h using a syringe pump. Continue stirring for 8 hours to obtain cellulose aqueous droplets with controllable particle size. (6) Heating the cellulose aqueous phase droplets with controllable particle size at 50℃ to make them semi-solid; (7) After heating for 1 hour, add 300 μL of epichlorohydrin to promote cross-linking between its molecules at close range; (8) After heating for another hour, add 300 μL of polypropylene glycol glycidyl ether to further promote long-distance cross-linking and curing between its molecules; (9) Continue heating overnight for 12 hours; (10) Stop heating and stirring, add deionized water and let stand to separate into layers. The upper layer is the oil phase and the lower layer is the water phase. The lower layer is milky white, that is, the cellulose microspheres are in the lower layer. Wash with water three times and then wash with petroleum ether. (11) Add 25 mL of 1% ethylenediamine solution, activate at 37°C for 24 hours, and wash repeatedly with water 3 times; (12) Transfer to ethanol for storage to obtain amino-activated cellulose microspheres with controllable particle size.

[0025] 2. Preparation of submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters (1) Preparation of solution A: Take 27 mL of ethylene glycol solution and place it in a container. Add 8.64 g of FeCl3·6H2O (optional mass range: 1-8.64 g). Sonicate at 45℃ for 20 min (optional sonication time range: 5-20 min) to fully dissolve it and form a homogeneous precursor solution. (2) Preparation of solution B: Take 27 mL of ethylene glycol solution, add 8.52 g of sodium acetate (optional addition range: 1-8.52 g), and stir magnetically at 650 rpm for 1 h at 55 °C to form a stable buffer system; (3) Preparation of solution C: Take 108 mL of ethylene glycol solution, add 2.82 g of sodium citrate (optional addition range: 1-2.82 g), and react with magnetic stirring at 650 rpm for 5 h at 55 °C (optional stirring time range: 1-5 h) to form a stable complex system; (4) Precursor mixing: Add solution B to solution A and mix evenly, then add solution C and 413 mg of PEG400-2000 (optional addition mass range: 5-413 mg), and sonicate at 45℃ for 60 min (optional sonication temperature range: 25-45℃, time range: 30-60 min) to form a homogeneous and stable reaction precursor solution; (5) Introducing cellulose microspheres: Cellulose microspheres (prepared in Example 1) that were pre-dispersed in the ethylene glycol phase were added to the reaction precursor solution, transferred to the reaction vessel, and reacted at 200°C for 24 h (optional reaction time range: 8-24 h) so that Fe3O4 nanocrystals were gradually generated on the surface and inside of the cellulose microspheres and achieved in-situ assembly to form a magnetic composite structure; (6) Product separation: After the reaction is completed, the supernatant is removed by an external magnetic field and the solid product is collected; (7) Washing and purification: The unreacted ions and residual organic matter were removed by magnetic separation washing twice each with deionized water and 50% ethanol solution. (8) Final collection: The precipitate is collected by magnetic separation to obtain sub-millimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters.

[0026] Colloidal micrographs of submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters are shown below. Figure 1 As shown, the results indicate that the sub-millimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters are regular spherical in shape, with good overall colloidal dispersion, no large-area severe agglomeration and sedimentation, and the particle size is mainly at the sub-millimeter level. Thus, a magnetic nanocrystal cluster colloidal material with regular morphology and stable dispersion was successfully synthesized.

[0027] Scanning electron microscope (SEM) image of submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters as shown below Figure 2 As shown, the results indicate that the surface of the cellulose microspheres is tightly packed with a large number of fine iron oxide nanoparticles, proving that iron oxide was successfully loaded onto the cellulose microspheres. The overall shape of the spheres is good, and the amount of iron oxide loaded is large and uniform, with strong encapsulation.

[0028] The magnetic response rate of submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters in deionized water is shown in the figure below. Figure 3As shown, the results indicate that after an external magnetic field is applied, the submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters exhibit good dispersion at 0 s and are basically adsorbed and aggregated at 1 s, which indicates that they have a fast magnetic response speed and strong magnetism.

[0029] The particle size distribution diagram of sub-millimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters is shown in the figure. Figure 4 As shown, the results indicate that the average particle size of the sub-millimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters is approximately 96.14316 μm.

[0030] Existing methods using magnetic magnetite colloidal nanoclusters have limitations: while they exhibit good magnetic adsorption in small volumes (few microspheres), the adsorption time and efficiency decrease as the volume increases. The adsorption state of submillimeter-sized superparamagnetic magnetite colloidal nanoclusters in large volumes of deionized water under an external magnetic field is illustrated in the diagram below. Figure 5 As shown, the results indicate that submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters still exhibit a fast magnetic response speed in a large volume state.

[0031] Example 2: (1) Take 100 mg of the sub-millimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters prepared in Example 1, and repeatedly magnetically wash them 3 times with 25 mM MES buffer (pH=5.0, free from amino and impurity alcohol interference). Each time, add 2 mL of buffer to resuspend the nanocrystals, and use an external permanent magnet to complete solid-liquid separation in 3 s. Discard the supernatant to completely remove the residual salts and dispersants from the synthesis.

[0032] (2) Prepare two activation solutions: a 200 mM EDC aqueous solution and a 100 mM Sulfo-NHS aqueous solution; add the solution to the washed... Add 1.8 mL of MES buffer to the crystal cluster, then add 100 μL of EDC aqueous solution and 200 μL of Sulfo-NHS aqueous solution in sequence. Invert and shake at room temperature in the dark for 30 min to complete the carboxyl activation. After activation, quickly separate by magnetic attraction, discard the activation waste liquid, and quickly rinse once with pre-cooled MES buffer to inhibit the hydrolysis of activated ester and retain highly active coupling sites.

[0033] (3) Weigh 12 mg of recombinant Protein A protein and dissolve it in 1 mL of MES coupling buffer (final protein concentration 12 mg / mL). Add the whole amount to the activated magnetic crystal cluster system and incubate at room temperature at low speed for 2 h. EDC / NHS mediates the formation of stable amide bonds between the carboxyl groups on the crystal cluster surface and the primary amino groups of Protein A molecules to achieve directional covalent fixation of ligands. After coupling, magnetically remove unbound free Protein A.

[0034] (4) Preparation of blocking solution: 0.1M Tris-HCl (pH=8.0, containing 1% BSA) was added to 2mL of blocking solution to resuspend the magnetic beads. The solution was incubated at room temperature for 1h to block unreacted activated carboxyl groups and eliminate non-specific protein adsorption. After blocking, the beads were washed 4 times with PBS-T buffer (pH=7.4, 0.05% Tween-20) to thoroughly wash away weakly bound contaminating proteins. Finally, the beads were resuspended in sterile PBS containing 0.02% ProClin300 antibacterial agent and stored at 4℃ in the dark to obtain ProteinA-functionalized magnetic cluster beads that can be directly used for the separation and purification of monoclonal / polyclonal antibodies.

[0035] (5) Ligand coupling efficiency test: Experimental reagents: BCA protein quantitative kit (solution A, solution B, 2 mg / mL BSA standard), supernatant of the coupling solution to be tested + all washing waste liquid, parallel preparation of Cytiva Protein A Ag Sepharose agarose magnetic beads and Thermo Pierce™ 88845 polystyrene polymer magnetic beads under the same conditions, three control groups, that is: BCA working solution was prepared according to the ratio of A:B=50:1, and each group Prepare 3 mL of working solution for each sample; in a 96-well plate, the total volume per well is 20 μL. Standards are prepared in gradients of 0, 1, 2, 4, 8, 16, and 20 μL, along with 2 mg / mL BSA. Add sterile water to a final volume of 20 μL. Take 10 μL of each waste solution and dilute it to 20 μL with 10 μL of sterile water. Add 200 μL of BCA working solution to each well. Incubate at 37°C for 30 min. Read the absorbance at 562 nm using a microplate reader. Calculate the free protein in each waste solution using a standard curve. Total mass of Protein A; Total mass of Protein A added in this study was 12 mg; Actual comparative data: Protein A functionalized magnetic cluster beads of this invention contained 1.08 mg of unbound free protein, with a covalent coupling efficiency of 91.0%; Cytiva agarose magnetic beads contained 4.92 mg of free protein, with a coupling efficiency of 59.0%; ThermoPierce™ 88845 magnetic beads contained 3.48 mg of free protein, with a coupling efficiency of 71.0%.

[0036] (6) Magnetic response speed and solid-liquid separation efficiency: Experimental consumables: 1.5mL standard plastic centrifuge tubes, uniformly sized square neodymium iron boron external permanent magnets, 1× sterile PBS buffer, electronic stopwatch; The operation and dosage are as follows: 50mg of each of the three groups of magnetic beads were accurately weighed, and 1mL of PBS buffer was added to each. The mixture was vortexed for 30s to completely disperse the beads. The sidewall of the centrifuge tube was pressed tightly against the outside of the permanent magnet. The stopwatch was used to record the time from when the magnet was placed until the solution in the tube was completely clear and free of suspended particles. The magnetic attraction-vortex resuspension cycle was repeated 10 times for each group, and the average separation time of the 10 cycles was taken. The measured comparison data are as follows: The average time for complete separation of ProteinA functionalized magnetic cluster beads in a single run is 2.8s; the average time for separation of Cytiva agarose beads is 62.4s; and the average time for separation of ThermoPierce™ 88845 beads is 24.7s. When processing antibody samples of the same volume in batches, the entire separation process of ProteinA functionalized magnetic cluster beads takes only 1 / 22 and 1 / 9 of that of Cytiva agarose beads and ThermoPierce™ 88845 beads, respectively, significantly improving solid-liquid separation efficiency.

[0037] (7) Antibody purification and product purity test: Reagent ratio: IgG cell culture supernatant (initial IgG concentration 1 mg / mL), PBST washing buffer, 0.1 M pH=2.7 glycine elution buffer, 1 M Tris neutralization solution (pH=9.0), SDS-PAGE reagent kit (12% separating gel, 5% stacking gel, 3× ​​protein loading buffer, electrophoresis buffer, Coomassie brilliant blue staining solution); Operation volume: Take 100 μL of magnetic bead slurry (solid content 50 mg / mL) from each of the three groups of Protein A magnetic beads, add 1 mL of IgG cell supernatant to each, invert and bind for 30 s at room temperature; discard waste liquid by magnetic aspiration, wash with 500 μL of PBST each time, repeat 3 rounds; add 100 μL of glycine elution buffer and let stand at room temperature for 2 min to elute IgG, immediately add 12 μL of 1 M Tris to neutralize the elution solution to neutral; take 20 μL of each group of IgG elution buffer to neutralize the elution solution. After neutralizing the elution buffer with μL, add 10 μL of 3× reducing loading buffer and boil in a water bath for 5 min. Perform electrophoresis at 80V for 30 min, then increase to 120V for 90 min. After staining and destaining, scan the gel. Quantify the IgG concentration at 280 nm using a UV spectrophotometer, and calculate the purity and recovery rate. Comparative data: The ProteinA-functionalized magnetic cluster beads of this invention eluted IgG with a purity of 96.4%, showing only two characteristic bands (heavy and light chains) and no obvious contaminating protein bands. Cytiva agarose beads eluted IgG with a purity of 83.7%, showing multiple contaminating bands. ThermoPierce™ 88845 beads eluted IgG with a purity of 88.2%, showing visible contaminating protein bands from the culture medium. Therefore, the IgG recovery rates were 92.3% for ProteinA-functionalized magnetic cluster beads, 68.6% for agarose beads, and 77.1% for polymer beads.

[0038] (8) Cyclic stability test: The three types of magnetic beads that have been eluted were thoroughly neutralized and washed with 1 mL of neutral PBS. The complete cycle of antibody binding-PBS washing-low pH elution was repeated 12 times. In each round, the remaining amount of ProteinA, the average time of magnetic separation, and the saturated binding capacity of IgG were measured. After 12 cycles, the antibody binding capacity of the ProteinA-functionalized magnetic cluster beads of the present invention was 90.7%, and the magnetic response time did not increase significantly. The capacity of the agarose magnetic beads was only 62.1%, and the gel broke down to produce fine suspended matter. The capacity of the Thermo polymer magnetic beads was 75.4%, and some magnetic beads agglomerated.

[0039] Conclusion: Under the same coupling conditions, the coupling efficiency of the Protein A functionalized magnetic cluster beads of this invention is higher than 90%, significantly better than Cytiva agarose magnetic beads and ThermoPierce™ 88845 polymer magnetic beads; the magnetic beads are integrally integrated. The nanocrystal clusters have no polymer insulating barrier layer and can completely settle within 3 seconds under an external magnetic field. Their magnetic response speed and batch solid-liquid separation efficiency are far superior to the two types of matrix magnetic beads on the market. The sub-millimeter particle size can completely avoid the risks of leakage of ultrafine nanoparticles and filter membrane penetration. The inert sealing layer on the surface of the magnetic beads greatly reduces the non-specific adsorption of impurities and proteins, and the purity of antibody elution products can reach more than 96%. After 12 acid-base regeneration cycles, the backbone does not peel off and the performance decay is minimal, making it more suitable for large-scale continuous purification production scenarios in biopharmaceuticals such as monoclonal antibodies and diagnostic antibodies.

[0040] The above description is merely an embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters, characterized in that, Includes the following steps: Step S1: Preparation of cellulose microspheres S101. Weigh sodium hydroxide, urea and distilled water, prepare an aqueous solution of sodium hydroxide / urea under ice bath conditions, and then pre-cool at -20℃. S102. Under ice bath conditions, cellulose powder is added to an aqueous solution of sodium hydroxide / urea and stirred to obtain a cellulose solution with a volume fraction of 4%. S103. Weigh out liquid paraffin and Span 80, mix and stir, then inject the cellulose solution into it and continue stirring to obtain cellulose aqueous droplets with controllable particle size. S104, heat the aqueous phase of cellulose with controllable particle size at 50℃, then add epichlorohydrin, continue heating, then add polypropylene glycol glycidyl ether, and continue heating. S105. Stop heating and stirring, add deionized water and let stand to separate the layers. The upper layer is the oil phase and the lower layer is the water phase. The lower layer is milky white, which means that the cellulose microspheres are in the lower layer. After washing, add 1% ethylenediamine solution and activate at 37°C. After washing, transfer to ethanol for storage to obtain amino-activated cellulose microspheres with controllable particle size. Step S2: Preparation of submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters S201. Add FeCl3·6H2O to an ethylene glycol solution and sonicate at 45°C to obtain solution A; add sodium acetate to an ethylene glycol solution and stir magnetically at 55°C to obtain solution B; add sodium citrate to an ethylene glycol solution and stir magnetically at 55°C to obtain solution C. S202. Add solution B to solution A and mix well. Then add solution C and PEG400-2000 at the same time. Sonicate at 25-45℃ to obtain the reaction precursor solution. S203. The cellulose microspheres pre-dispersed in the ethylene glycol phase are added to the reaction precursor solution and reacted at 200°C to form a magnetic composite structure. S204. After the reaction is complete, the supernatant is removed by an external magnetic field separation method, the solid product is collected, and after washing, the precipitate is collected by magnetic separation method to obtain submillimeter-sized superparamagnetic iron oxide colloidal nanocrystal clusters.

2. The preparation method according to claim 1, characterized in that, In S101, sodium hydroxide, by mass ratio: Urea: Distilled water = 7:12:

81.

3. The preparation method according to claim 1, characterized in that, S103 is specifically prepared as follows: Weigh 80 ml of liquid paraffin and 20 ml of Span 80, mix them and add them to a three-necked flask, stir at 400 rpm for 1 h; take 15 ml of cellulose solution, use a syringe pump to inject it into the three-necked flask at a speed of 1~15 ml / h through a microporous membrane, and continue stirring for 8 h to obtain cellulose aqueous droplets with controllable particle size.

4. The preparation method according to claim 1, characterized in that, In S105, activation is performed at 37°C for 24 hours.

5. The preparation method according to claim 1, characterized in that, Specifically, S201 involves: placing 27 mL of ethylene glycol solution in a container, adding 1-8.64 g of FeCl3·6H2O, and sonicating at 45°C for 5-20 min to obtain solution A; taking 27 mL of ethylene glycol solution, adding 1-8.52 g of sodium acetate, and reacting at 55°C with magnetic stirring at 650 rpm for 1 h to obtain solution B; and taking 108 mL of ethylene glycol solution, adding 1-2.82 g of sodium citrate, and reacting at 55°C with magnetic stirring at 650 rpm for 1-5 h to obtain solution C.

6. The preparation method according to claim 1, characterized in that, S202 is specifically as follows: Add solution B to solution A and mix thoroughly, then add solution C, and simultaneously add 5-413 mg of PEG400-2000. Sonicate at 25-45℃ for 30-60 min to form a homogeneous and stable reaction precursor solution.

7. The preparation method according to claim 1, characterized in that, In S203, the reaction is carried out at 200℃ for 8-24 hours.

8. The preparation method according to claim 1, characterized in that, In S204, magnetic separation washing is performed twice each using deionized water and 50% ethanol solution.

9. Submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters, characterized in that they are prepared by the preparation method of submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters according to any one of claims 1-8.

10. The application of the submillimeter-scale superparamagnetic iron oxide colloidal nanocrystal clusters as described in claim 9 in the rapid magnetic separation and enrichment of diagnostic antibodies.

Citation Information

Patent Citations

  • Monodisperse superparamagnetic nano crystal colloidal core-shell composite particles and preparation method thereof

    CN103342393A

  • Superparamagnetic nano-particles, magnetic beads and preparation method and application of superparamagnetic nano-particles and magnetic beads

    CN117334425A